Assessment of Statistical Process Control Based DVH Action Levels for Systematic Multi-Leaf Collimator Errors in Cervical Cancer RapidArc Plans - Zhang, Hanyin; Lu, Wenli; Cui, Haixia; Li, Ying; Yi, Xin (Frontiers in Oncology, 2022)
Background: The aim of this study is to explore reasonable DVH-based action levels and optimal DVH metrics in detecting systematic MLC errors for cervical cancer RapidArc plans. Methods: A total of 148 cervical cancer RapidArc plans were selected and measured with COMPASS 3D dosimetry system. Firstly, the patient-specific QA results of 110 RapidArc plans were retrospectively reviewed. Then, DVH-based action limits (AL) and tolerance limits (TL) were obtained by statistical process control. Secondly, systematic MLC errors were introduced in 20 RapidArc plans, generating 380 modified plans. Then, the dose difference (DE%) in DVH metrics between modified plans and original plans was extracted from measurement results. After that, the linear regression model was used to investigate the detection limits of DVH-based action levels between DE% and systematic MLC errors. Finally, a total of 180 test plans were prepared for validation. The positive rate of DVH-based action levels in detecting error-induced plans were compared in different DVH metrics. Results: A linear correlation was found between systematic MLC errors and DE% in all DVH metrics. Based on linear regression model, the systematic MLC errors of -0.94 mm and 0.88 mm could be caught by the TL of PTV95 ([-1.54%, 1.51%]), and the systematic MLC errors of -1.00 mm and -0.80 mm could also be caught by the TL of PTVmean ([-2.06%, 0.38%]). In the validation, for original plans, PTV95 showed the minimum positive rate of 5.56%. For error-introduced plans with systematic MLC errors more than 1mm, PTVmean showed the maximum positive rate of 88.89%, and then was followed by PTV95 (86.67%). All the TL of DVH metrics showed a poor positive rate in identifying error-induced plans with systematic MLC errors less than 1mm. Conclusion: Process-based tolerance limits showed greater advantages in distinguishing plans with systematic MLC errors more than 1mm, and reasonable DVH-based action levels can be acquired through statistical process control. During DVH-based verification, main focus should be on the DVH metrics of target volume. OARs in low-dose regions were found to have a relatively higher dose sensitivity to smaller systematic MLC errors, but may be accompanied with higher false positive rate.